Deployment of organic farming at a landscape scale maintains low pest infestation and high crop productivity levels in vineyards. Issue 3 (29th November 2017) - Muneret, Lucile; Thiéry, Denis; Joubard, Benjamin; Rusch, Adrien
Abstract: Organic farming is a promising way to reduce pesticide use but increasing the area under organic farming at the landscape scale could increase pest infestations and reduce crop productivity. Examining the effects of organic farming at multiple spatial scales and in different landscape contexts on pest communities and crop productivity is a major step in the ecological intensification of agricultural systems. We quantified the infestation levels of two pathogens and five arthropod pests, the intensity of pesticide use and crop productivity in 42 vineyards. Using a multi‐scale hierarchical design, we unravelled the relative effects of organic farming at both field and landscape scales from the effects of semi‐natural habitats in the landscape. At the field scale, pest communities did not differ between organic and conventional farming systems. At the landscape scale, increasing the area under organic farming did not increase pest infestation levels. Three out of seven pest taxa were affected both by local farming systems and the proportion of semi‐natural habitats in the landscape. Our findings revealed that the proportion of semi‐natural habitats reduced pest infestation for two out of seven pest taxa. Organic vineyards had much lower treatment intensities, very similar levels of pest control and equal crop productivity levels. Synthesis and Applications . Our results clearly indicate that policies promoting the development of organic farming in conventional vineyard landscapes will not lead to greater pest and disease infestations but will reduce the pesticide treatment intensity and maintain crop productivity. Moreover, the interactions between semi‐natural habitats in landscape and local farming practices suggest that the deployment of organic farming should be adapted to landscape contexts. Abstract : Our results clearly indicate that policies promoting the development of organic farming in conventional vineyard landscapes will not lead to greater pest and disease infestations but will reduce the pesticide treatment intensity and maintain crop productivity. Moreover, the interactions between semi‐natural habitats in landscape and local farming practices suggest that the deployment of organic farming should be adapted to landscape contexts.